China's Eurasian pivot the Silk Road economic belt - Pantucci, Raffaello; Lain, Sarah (Whitehall paper series, 2017)
"This Whitehall Paper is an examination of China's relations over its western borders, looking at the interplay between China's relations with South and Central Asia, and its relations with other great adjacent powers. Based on a two-year research project that included travel and workshops in South and Central Asia, this Paper examines Beijing's changing impact and relationship with its near neighbourhood. Conceived prior to the announcement of Xi Jinping's 'Belt and Road Initiative' research for this report was undertaken in the shadow of the September 2013 announcement and the 'Belt and Road' ultimately proved to be the driving framework under which this report was drafted. The report sketches out the roots of the initiative, and how it is being felt on the ground, exploring in detail how it is being received in China's immediate neighbourhood where its impact is most significant for China."--Provided by publisher